2015
DOI: 10.1128/aem.03840-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanisms of Murine Norovirus Inhibition by Pulsed-Light Technology

Abstract: Pulsed light is a nonthermal processing technology recognized by the FDA for killing microorganisms on food surfaces, with cumulative fluences up to 12 J cm ؊2 . In this study, we investigated its efficacy for inactivating murine norovirus 1 (MNV-1) as a human norovirus surrogate in phosphate-buffered saline, hard water, mineral water, turbid water, and sewage treatment effluent and on food contact surfaces, including high-density polyethylene, polyvinyl chloride, and stainless steel, free or in an alginate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 58 publications
2
27
0
2
Order By: Relevance
“…Therefore, the development of novel nonthermal technologies for viral decontamination of foods is of great interest to food scientists and food producers. A few studies are available on the virucidal effects of such technologies to combat foodborne viral contamination, e.g., ozone treatment (20), gamma irradiation (17), lactic acid bacteria used as an antiviral biopreservative (1), pulsed-light technology (38), and, most recently, cold atmospheric pressure gaseous plasma (2). Another growing trend of investigation is the exploration of natural compounds for their antiviral properties.…”
mentioning
confidence: 99%
“…Therefore, the development of novel nonthermal technologies for viral decontamination of foods is of great interest to food scientists and food producers. A few studies are available on the virucidal effects of such technologies to combat foodborne viral contamination, e.g., ozone treatment (20), gamma irradiation (17), lactic acid bacteria used as an antiviral biopreservative (1), pulsed-light technology (38), and, most recently, cold atmospheric pressure gaseous plasma (2). Another growing trend of investigation is the exploration of natural compounds for their antiviral properties.…”
mentioning
confidence: 99%
“…In case of murine norovirus, Vimont et al . () also found that PL disrupts MNV‐1 structure and degrades viral proteins and RNA. On the other hand, Nicorescu et al .…”
Section: Pl‐induced Cellular Damage Of Micro‐organismsmentioning
confidence: 88%
“…Viruses like murine norovirus as a surrogate for human norovirus have also been proven to be sensitive to PL exposure in different matrices, reaching reductions of viral infectivity by more than 3 log units with 3·45–7·6 J cm −2 (Vimont et al . ). A range of viruses like herpes simplex virus type 1 and nonenveloped viruses, that is, encephalomyocarditis, polio virus type 1, hepatitis A (HAV), bovine parvovirus and canine parvovirus have been shown to be PL sensitive, revealing inactivation of >4·8–>7·8 log with 1 J cm −2 (Roberts and Hope ).…”
Section: Relevant Factors Affecting Microbial Inactivation In Pl Expementioning
confidence: 97%
“…The mechanism involved in antiviral activity of PL is probably disruption of viral structure that ultimately degrades viral proteins and RNA. PL at 12 J/cm 2 with 3-6 s exposure resulted in > 3.0 log 10 reduction of MNV in various liquids (Vimont et al, 2015). PL or UV may be used in combination with other control strategies (e.g.…”
Section: Light Based Technologiesmentioning
confidence: 99%